Digital Zakat and Waqf for Environmental Sustainability: A Global Bibliometric and Thematic Review - Haryani Santo Hartono; Fahad Babangida (Program Studi Magister Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Sunan Kalijaga, 2025)
Zakat and waqf are being seen as strategic applications in the realm of Islamic social finance as a tool to promote sustainable development. Although many studies focused on their role in solving poverty and social economic inequality, they have little depicted little in the realms of literature dealing with environmental sustainability. This paper aims to analyze how the concept of digital transformation of zakat and waqf is presented in the academic discourse in order to answer the environmental concerns. This paper adopts a bibliometric and thematic study to trace the cycle of global academic outputs, in the context of papering on zakat, waqf, digital innovation and environmental goals- as identified in Scopus database. An analysis also identifies some of the central themes of sustainability, developing ideas like green waqf, and the use of the digital platforms within financing the development of sustainable environmental projects. It is also reflective of how well these tools serve the purpose of Maqasid al-Shariah and the sustainability agenda on a global scale. This review will produce findings that can be useful to the understanding of gaps in research, as well as leading to the establishment of the path to support the improvement in the role that zakat and waqf can play on the environment through innovation and intersectoral collaboration. This helps to further the changes of Islamic charity in the age of the digital world.